2019
DOI: 10.3389/fpsyg.2019.01126
|View full text |Cite
|
Sign up to set email alerts
|

Flow Experiences During Visuomotor Skill Acquisition Reflect Deviation From a Power-Law Learning Curve, but Not Overall Level of Skill

Abstract: Flow is a state of “optimal experience” that arises when skill and task demands match. Flow has been well studied in psychology using a range of self-report and experimental methods; with most research typically focusing on how Flow is elicited by a particular task. Here, we focus on how the experience of Flow changes during task skill development. We present a longitudinal experimental study of learning, wherein participants ( N = 9) play a novel steering-game task designed to elicit Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The version used here is based on an existing PANAS translation which was slightly modified by PP and MT. The FSS used was the translation used in Cowley et al (2019) with some slight edits.…”
Section: Methodsmentioning
confidence: 99%
“…The version used here is based on an existing PANAS translation which was slightly modified by PP and MT. The FSS used was the translation used in Cowley et al (2019) with some slight edits.…”
Section: Methodsmentioning
confidence: 99%
“…The improved performance was manifested in improved temporal perception (i.e., reduced JND scores) and significantly improved spatial attentional control (i.e., reduced PSS scores) when flow states were highest. In a recent longitudinal experiment by Cowley et al (2019), where flow was induced with the help of a video game-like high-speed steering task, possible trial-wise fluctuations of performance due to flow were found, suggesting that performance was enhanced when participants experienced increased flow. These results dovetail with our findings, and might likewise indicate a short-term modulation of information processing and performance by flow.…”
Section: Discussionmentioning
confidence: 99%
“…The Flow Short Scale reflects Rheinberg's [73] conceptualisation of flow, which does not include autotelicity, and loads onto two underlying dimensions of fluency of performance and absorption. The Flow Short Scale has tended to be more widely used within gaming studies and those employing psychophysiological measures, and was used in eight of the reviewed studies, five in gaming [47,55,58,60,62] and three in sport [61,68,69]. The Flow State Scale and Dispositional Flow Scale have been more prominent within sport research and were used in eight studies, all of which used sporting tasks [45,54,59,63,[65][66][67]70].…”
Section: Methods Of Measuring Flowmentioning
confidence: 99%
“…Studies have generally not controlled for prior or 'normal' performance, so if flow is more likely in more skilled performers then a flow-performance relationship could emerge for this reason alone. One article from the review, Cowley et al [58], suggests that this is, however, not the case. In a longitudinal design Cowley and colleagues showed that there was no change in the experience of flow as participants acquired expertise in a driving game.…”
Section: Conceptual and Methodological Issuesmentioning
confidence: 99%
See 1 more Smart Citation